Engaging theories in family communication multiple perspectives - Braithwaite, Dawn O.; Suter, Elizabeth; Floyd, Kory (Routledge, Taylor & Francis Group, 2018)
"Engaging Theories in Family Communication, Second Edition delves deeply into the key theories in family communication, focusing on theories originating both within the communication discipline and in allied disciplines. Contributors write in their specific areas of expertise, resulting in an exceptional resource for scholars and students alike, who seek to understand theories spanning myriad topics, perspectives, and approaches."--Provided by publisher.